Efficacy and safety of traditional Chinese medicine combined with azithromycin sequential therapy for mycoplasma pneumonia among children: a meta-analysis of randomized controlled trials - Lyu, Jing; Fan, Fei; Li, Ji; Wang, Qiong; Tian, Xue; Xu, Jiaxing; Zhang, Si; Wang, Bo (Frontiers in Pharmacology, 2024)
Background: Traditional Chinese medicine (TCM) is used to treat mycoplasma pneumonia (MP) in children with favorable treatment outcome in China. In the present study, we evaluated the clinical efficacy of TCM combined with azithromycin (AZM) for the treatment of MP among children, providing high evidence-based reference for clinical treatment. Method: We retrieved eligible randomized controlled trials (RCTs) from CQVIP, CNKI, WanFang, NSTL, PubMed, Embase, and Embase databases from January 2000 to November 2023. Data extraction and quality assessment of the enrolled studies were independently by two reviewers. Review Manager 5.3 was used for meta-analysis. Result: A total of 51 RCTs involving 5,799 children aged 1–14 enrolled. Meta-analysis demonstrated that TCM combined with AZM improved the cure rate ( odds ratio [OR] = 2.34, 95% CI: 2.06 to 2.64,) and the effective rate (OR = 5.21, 95% CI: 4.22 to 6.43, ), shorted the disappearance duration of cough (WMD = -1.62, 95% CI: -1.90 to -1.34, ), the duration of fever (WMD = -1.62, 95% CI: -1.96 to -1.29,), and the disappearance time of lung rales (WMD = -1.15, 95% CI: -1.32 to -0.98, ), improved CRP levels (WMD = -2.06, 95% CI: -2.57 to -1.55, ), IL-6 levels (WMD = -1.92,95% CI: -2.51 to -1.34, ), and TNF-α levels (WMD = -1.59, 95% CI: -2.14 to -1.04 ), and reduced adverse reactions (OR = 0.37, 95% CI: 0.32 to 0.44, ). Conclusion: TCM combined with AZM in the treatment of MP among children has favorable clinical efficacy and safety.